Advances in sciatic nerve regeneration: A review of contemporary techniques - Sardar Ali; Ming Sun; Muhammad Nadeem Khan; Fang Qiang (Regenerative Therapy)
Sciatic nerve injury, affecting the longest and thickest nerve in the human body, often leads to severe pain, weakness, and impaired motor function in the lower extremities. Despite the peripheral nervous system's inherent capacity for some degree of regeneration, complete recovery remains elusive, necessitating advanced therapeutic approaches. This review explores two promising modalities electrical stimulation (ES) and platelet-rich plasma (PRP) that have shown the potential to enhance nerve repair and functional recovery. ES, through techniques such as transcutaneous electrical nerve stimulation (TENS), neuromuscular electrical stimulation (NMES), and direct current stimulation (DCS), facilitates neuronal regeneration by guiding axonal growth, releasing neurotrophic factors, and promoting synaptic plasticity. PRP, derived from autologous blood, is rich in growth factors such as Platelet-derived growth factor (PDGF), vascular endothelial growth factor (VEGF), and nerve growth factor (NGF), which are essential for nerve regeneration, angiogenesis, and reducing inflammation. Clinical evidence supports the efficacy of ES and PRP in promoting nerve regeneration and functional recovery (Figure 1). However, further research is needed to optimize their application and understand their long-term outcomes. This review highlights the potential of these therapies to capitalize on their actions, potentially creating a robust regenerative milieu. Further research is needed to optimize treatment procedures and validate their efficacy and safety in humans.